Evaluation of the cementite morphology influence on the hydrogen induced crack nucleation and propagation path in carbon steels - Shabnam Karimi (19457575) (2022)
The effect of cementite morphology on the crack initiation and growth path was studied using in situ electrochem-ical micro-cantilever bending (ECCB) technique under hydrogen (H) charging. Two carbon steels with lamellar cementite morphology (pearlitic microstructure) and spherical or broken lamellas cementite morphology (spheroidite microstructure), both with approximately the same carbon equivalent, were used in this study. The ECCB tests were performed in H-free and two H charging steps with −1050 mV and −1550 mV charging potential versus Ag/AgCl reference electrode. The results show that both materials are resistant to crack initiation in the H-free condition while under −1050 mV charging, crack propagates through the grain boundaries in a tortuous path in spheroidite mi-crostructure and the lamellar microstructure displayed a higher strength with small cracks propagating through both the grain boundaries and the lamellas. A drastic load decrease in the load-displacement (L-D) curve happened under −1550 mV charging for both microstructures accompanied by a straight crack growth path in spheroidite microstruc-ture, independent of grain boundaries or ferrite-cementite interfaces while a competition between the shear crack growth mechanism and the interfacial cracking determines the crack growth path in the lamellar microstructure. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2022.01.222